The role of water content in rate dependence of tensile strength of a fine-grained sandstone - Cai, Xin; Cheng, Chuanqing; Zhao, Yuan; Zhou, Zilong; Wang, Shaofeng (Archives of Civil and Mechanical Engineering, 2022)
Rocks in nature are commonly in partially saturated conditions and exposed to dynamic loads. In this study, to explore the coupled effects of water content and loading rate, dynamic Brazilian disc experiments were conducted on Yunnan sandstone samples with four levels of water content (from air-dried to water-saturated) under various loading rates (from 100 to 600 GPa/s) using a split Hopkinson pressure bar. The test results show that for each water content, the dynamic tensile strength of sandstone is positively sensitive to loading rate. The rate dependence of tensile strength increases as the rise of water content. The change trends of tensile strength against water content depend on loading rate: as water content rises, the tensile strength displays the manner of “no change followed by fast drop” at loading rates of 10 –4 and 100 GPa/s. However, when the loading rate is above 200 GPa/s, the tensile strength increases first and then declines. The turning point occurs at water content between 1.0 and 2.0%. These observations can be interpreted with the competition between water weakening and enhancing effects under different loading conditions.